Proceedings of the 38th International Symposium on Symbolic and Algebraic Computation 2013
DOI: 10.1145/2465506.2465516
|View full text |Cite
|
Sign up to set email alerts
|

Cylindrical algebraic decompositions for boolean combinations

Abstract: This article makes the key observation that when using cylindrical algebraic decomposition (CAD) to solve a problem with respect to a set of polynomials, it is not always the signs of those polynomials that are of paramount importance but rather the truth values of certain quantifier free formulae involving them. This motivates our definition of a Truth Table Invariant CAD (TTICAD). We generalise the theory of equational constraints to design an algorithm which will efficiently construct a TTICAD for a wide cl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
117
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 35 publications
(117 citation statements)
references
References 24 publications
0
117
0
Order By: Relevance
“…7 Proportion of x1 occuring in polynomials. 8 Proportion of x2 occuring in polynomials. 9 Proportion of x0 occuring in monomials.…”
Section: Featuresmentioning
confidence: 99%
“…7 Proportion of x1 occuring in polynomials. 8 Proportion of x2 occuring in polynomials. 9 Proportion of x0 occuring in monomials.…”
Section: Featuresmentioning
confidence: 99%
“…A key improvement to CAD has been in the projection operator to reduce the number of projection polynomials computed (Hong, 1990;McCallum, 1998McCallum, , 1999bMcCallum, , 2001Brown, 2001;Bradford et al, 2013a;Han et al, 2014;Bradford et al, 2016).…”
Section: Projection Operatorsmentioning
confidence: 99%
“…We build on recent work by Bradford et al (2016) to measure the dominant term in bounds on the number of CAD cells produced. Numerous studies have shown this to be closely correlated to the computation time (Dolzmann et al, 2004;Bradford et al, 2013aBradford et al, , 2014. We assume CAD input with m polynomials of maximum degree d in any one of n variables.…”
Section: Complexity Analysis Of Cad With Ecmentioning
confidence: 99%
“…NuCAD and the model-based construction also provide a natural way to take strong advantage of the particulars of the input formula from which the decomposition is constructed. Much of what has been done in the way of CAD research has been based on trying to do exactly this: partial CAD, equational constraints [7,11], divide & conquer [14], and truth table invariant CAD [1], for example. This paper's contributions are the introduction of the Open NuCAD, a model-based algorithm for efficiently constructing NuCADs along with a proof of correctness, and empirical data demonstrating how much more efficiently NuCAD represents semi-algebraic sets than CAD.…”
Section: Illustrates Thismentioning
confidence: 99%